Impact of Globalization on Organizational Culture: A Case of Nepalese Organizations - Bhatta, Ingit (Nepalese Journal of Business, 2024)
This study examines the impact of globalization on organizational culture: A case of Nepalese organizations. Employee satisfaction is the dependent variable. The selected independent variables are leadership style, geographical diversity, communication technology, organizational structure and training & development. The primary source of data is used to assess the opinions of respondents regarding leadership style, geographical diversity, communication technology, organizational structure and training & development. The study is based on primary data of 111 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of globalization on organizational culture: A case of Nepalese organizations. The study showed a positive impact of leadership style on employee satisfaction. It indicates that effective leadership style leads to increase in employee satisfaction. Similarly, the study showed a positive impact of geographical diversity on employee satisfaction. It indicates that employee from different geographic diversity have different abilities which increase the level of employee satisfaction. Likewise, the study also revealed a positive impact of communication technology on employee satisfaction. It indicates that effective communication & technology lead to increase in employee satisfaction. Further, the study observed a positive impact of organizational structure on employee satisfaction. It indicates that attractive organizational structure leads to increase in employee satisfaction. Moreover, the study observed a positive impact of training & development on employee satisfaction. It indicates that higher the number of training & development programs conducted by the organizations for employees, higher would be the employee satisfaction.